Computer Wish List from Ann L. Adams to Sam Ellis - Ann L. Adams (1993)
This document was on a 5.25" floppy disk that was put in the time capsule. It is a letter from Ann L. Adams to Sam Ellis requesting funding for various computer services. The second document includes the requested amounts adjusted for 2018 inflation.